Is acupuncture effective against pain in patients with Parkinson’s disease? A randomized controlled study - Yaksi, Elif; Yasar, Mustafa Fatih; Dogan, Nalan; Balci, Muhammed (EXPERIMENTAL BIOMEDICAL RESEARCH, 2022)
Aim: To investigate the efficacy of acupuncture application in the treatment of neck pain of musculoskeletal origin in patients with Parkinson’s disease (PD). Methods: Forty-five patients were screened, of whom 40 were enrolled and 29 completed the study. The patients were divided into two groups, each consisting of 20 individuals. The acupuncture group (AG) received acupuncture therapy in addition to neck exercises, while the control group (CG) performed only neck exercises. Both groups were enrolled in an exercise program, every day of the week for five weeks. The AG also received 10 sessions of acupuncture, twice weekly. The Hoehn and Yahr Scale, the Visual Analog Scale (VAS), the Movement Disorder Society Unified Parkinson's Disease rating Scale-I (MDS-UPDRS-I), a Health Assessment Questionnaire (HAQ), and the Neck Disability Index (NDI) were applied as data collection tools before and at the end of treatment. Results: Significant improvement was determined in both groups in post-treatment VAS, MDS-UPDRS-I, HAQ, and NDI values compared to pre-treatment (p<0.05). The improvement in VAS, MDS-UPDRS-I, HAQ, and NDI values was significantly greater in AG than in CG (p<0.05). Conclusion: With its local and systemic effects, acupuncture is a safe procedure capable of use for analgesia. However, further randomized, placebo-controlled studies will permit a more detailed evaluation of its therapeutic efficacy.